Penanaman Adab di Pesantren Tahfidzul Qur’an Sains Ar-Risalah - Az Zahrah, Fathimah; Muslimah, Fadhilah Wardatul; Anshory, Muhammad Isa (Lembaga Yasin AlSys, 2025)
Adab of santri refers to the behavior exhibited by students in their daily lives, both within and outside the pesantren. Variations in personality are natural, as students come from diverse family and cultural backgrounds. One of the defining characteristics of a pesantren is its role as a place where students learn and develop into individuals with noble character and proper etiquette. The formation of a santri’s etiquette naturally involves gradual stages and habitual practices established through structured rules. Therefore, Pondok Pesantren Tahfidzul Qur’an Sains Ar Risalah Solo serves as an intriguing case for studying the process of cultivating etiquette among its female students. This research employs a field study approach, utilizing observation and interviews with the teachers as the primary methods.